Absorptive capacity and achieving the MDGs - François Bourguignon; Mark Sundberg (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The ability of low-income countries to productively absorb large amounts of external assistance is a central issue for efforts to scale-up aid. This paper examines absorptive capacity in the context of MDG-based development programmes in low-income countries. It first defines absorptive capacity, and proposes a framework for measuring it. Applying a dynamic computable general equilibrium model to link the macro framework to sector results, the paper simulates MDG scenarios for Ethiopia and examines the role of infrastructure, skilled labour, macroeconomic, and other constraints on absorptive capacity. The main policy conclusions are that careful sequencing of public investment across sectors is key to minimizing the costs of reaching the MDGs; the macro impact of large aid flows on the tradeables sector can potentially be serious in the short run; large-scale frontloading of aid disbursements can be costly as it pushes against absorptive constraints; and that improvement of governance and institutional structures can significantly reduce the cost of achieving the MDGs.
Keywords: O11; O15; O21; 330; aid; absorptive capacity; Millennium Development Goals; Entwicklungshilfe; Millennium Development Goals; Low-Income Countries